2010
DOI: 10.1007/s12031-010-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Pituitary Adenylate Cyclase-Activating Polypeptide in the Human Placenta during Pregnancy and Its Effects on the Survival of JAR Choriocarcinoma Cells

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP), a neuropeptide with survival-promoting actions, has been observed in endocrine organs and is thought to play a role in reproductive functions, including pregnancy. PACAP occurs in two forms, 27 and 38 amino acid residues, with PACAP38 being the predominant form in human tissues. In the present study, we determined the concentrations of PACAP38 and PACAP27 in first-trimester and full-term human placentas using radioimmunoassay. We found high levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…These authors found no immunoreactive nerve fibers in the placenta or umbilical cord, immunoreactive nerve fibers were only present in the uterus, with isthmic region and nonpregnant myometrium showing stronger immunoreactivity than pregnant uterus. PACAP immunoreactivity by radioimmunoassay was confirmed later by Brubel et al [39]: both forms of the peptide could be detected with PACAP38 23 Occurrence and Functions of PACAP in the Placenta showing stronger immunoreactivity, in agreement with the above earlier observations. Furthermore, it was also found that different parts of the human placenta contained similar levels of PACAPs, such as central maternal, peripheral maternal, central fetal, and peripheral fetal parts.…”
Section: Occurrence Of Pacap and Pacap Receptors In The Placentasupporting
confidence: 85%
See 2 more Smart Citations
“…These authors found no immunoreactive nerve fibers in the placenta or umbilical cord, immunoreactive nerve fibers were only present in the uterus, with isthmic region and nonpregnant myometrium showing stronger immunoreactivity than pregnant uterus. PACAP immunoreactivity by radioimmunoassay was confirmed later by Brubel et al [39]: both forms of the peptide could be detected with PACAP38 23 Occurrence and Functions of PACAP in the Placenta showing stronger immunoreactivity, in agreement with the above earlier observations. Furthermore, it was also found that different parts of the human placenta contained similar levels of PACAPs, such as central maternal, peripheral maternal, central fetal, and peripheral fetal parts.…”
Section: Occurrence Of Pacap and Pacap Receptors In The Placentasupporting
confidence: 85%
“…A similar effect was observed in cells undergoing chemically induced hypoxia by CoCl 2 . No effects on survival were observed in cells exposed to lipopolysaccharide (LPS), methotrexate or ethanol [39,53]. These findings were contradicting the general survival-promoting effect of PACAP observed in many different cell lines and tissues both in vitro and in vivo [54].…”
Section: Effects Of Pacap On Survival Of Trophoblast Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…While in most cell types PACAP is protective, in some tumors it exerts toxic effects [ 111 ]. Furthermore, PACAP6-38 is in most cell types an antagonist, it can also behave as an agonist in some, tumorous and even non-tumorous, cells [ 112 , 113 ].…”
Section: Studies In Tumor Cellsmentioning
confidence: 99%
“…The homogenate was centrifuged (12,000 rpm, 4°C, 30 min), and the supernatant was further processed for RIA analysis of PACAP38-LI and PACAP27-LI with a specific and sensitive RIA technique developed in our laboratory (Jakab et al 2004;Nemeth et al 2007;Borzsei et al 2009;Brubel et al 2010), and concentrations of the peptide were calculated with the help of a calibration curve. Briefly: Antiserum: PACAP38 B88111-3^(working dilution 1:10,000) and PACAP27 B88123^(dilution 1:45,000).…”
Section: Radioimmunoassay Examinationmentioning
confidence: 99%